Effects of thermal and elastic deformations on lubricating properties of the textured journal bearing. (October 2019) - Zhang, Yu; Chen, Guoding; Wang, Lin
Hydrodynamic journal bearing is an important part of rotary machine and faces many challenges such as high rotating speed, heavy specific pressure, and large temperature rise with the development of industry. These challenges lead to notable thermal and elastic deformations of the journal bearing. Surface texture has been proved to be a valid method to promote bearing lubricating properties. However, effects of thermal and elastic deformations on lubricating properties of the textured journal bearing have not been clearly analyzed. Based on this, the article presents a method to transform thermal–structural–fluid interaction into thermal–structural interaction and thermal–fluid interaction based on textured journal bearing model. Cavitation and temperature-viscosity effects are also considered. Based on this method, action mechanisms of surface texture on lubricating properties are discussed considering elastic and thermal deformations, and effects of elastic and thermal deformations on the textured journal bearing are also investigated. The results show that the load carrying capacity and the maximum oil film pressure of the textured journal bearing both increase when elastic and thermal deformations are considered. Optimal texture parameters can enhance the backflow effect in dimples and restraint cavitation phenomenon in the oil film rupture region. Meanwhile, inertial and cavitation effects caused by surface texture have significant effects on elastic and thermal deformations of the journal bearing.